(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
This paper surveys the existing Technology transfer (TT) models developed across different industries. The aim is to develop and empirically test a model that describes the TT process of embracing foreign advanced technology by ICT and ICT-based SME projects in Libya. The developed model defines the following factors (enablers) that influence the ITT process, which is TT government support initiatives, transferor characteristics, transferee characteristics, TT environment, learning centers, and their respective sub-factors (variables). The outcome (achievements) factors are identified and explained through their relevant sub-factors. To verify the model and investigate the interrelations between the model’s factors a questionnaire survey was conducted in Libyan ICT projects where the TT process was involved. Statistical analysis methods were used to analyze the data collected. The respondents indicated that transferee’s characteristics were the most important factor with the highest impact that will result in an effective TT process. Moreover, the results showed that most factors chosen for this study are relevant towards an effective TT process. Economic development was perceived to be the most meaningful outcome of a successful TT process, followed by knowledge improvement, the firm’s performance, and development as well as the survival of ICT-based SMEs. This paper is a part of an ongoing study to develop ITT model for the Libyan ICT industry.